From Model to Action: Identifying the Gaps in Coastal Marsh Models for Decision Making - Amanda D. Stoltz; Dawn M. Kotowicz; Christine Addison Buckel; Davina L. Passeri; Renee Collini; Nina Woodard; Sara Martin (Wetlands, 2026)
Coastal salt marsh modeling projects are designed to answer questions about where salt marshes may migrate, how they can migrate, and how they will be impacted by changing water levels. While this information is vital for climate-resilient marsh conservation, translating these findings into actionable results remains a challenge. The authors examined the actionability of marsh modeling efforts in the United States by analyzing data collected from semi-structured interviews of marsh model users ( n = 24) across two ongoing projects along the U.S. East Coast and the Gulf of America (Gulf of Mexico). By qualitatively analyzing the interview data, the authors found that the tasks of practitioners who use coastal marsh model outputs fall into three major themes: (1) marsh restoration, (2) planning with uncertainty, and (3) conserving habitat for marsh-reliant species. For each of these themes, the authors identify unmet needs, including high spatial resolution information for local planning, accessible descriptions of uncertainty to increase user confidence, and the incorporation of human dimensions data (e.g., human alterations to the landscape such as impoundments and culverts) for a comprehensive understanding of the coastal salt marsh. Marsh modeling projects should strategize how to fulfil these unmet user needs so that marsh modeling outputs can better support decisions related to marsh conservation and restoration.

Nature-based solutions as buffers against coastal compound flooding: Exploring potential framework for process-based modeling of hazard mitigation - Soheil Radfar; Sadaf Mahmoudi; Hamed Moftakhari; Trevor Meckley; Matthew V. Bilskie; Renee Collini; Karim Alizad; Julia A. Cherry; Hamid Moradkhani (Science of The Total Environment, 2024)

Sea Grant Programs Build Resilience to Coastal Climate Hazards - Ian Miller; Mary Collins; Michelle Covi; Parker Gassett; Holly Abeels; Karina Alvarez; Juliana Barrett; Savanna Barry; Mona Behl; Renee Collini; Laura Engeman; Phyllis Grifman; et al. (Oceanography, 2024)
Sea Grant programs across the United States and its territories are working with coastal communities to enhance their resilience to hazards and weather extremes exacerbated by climate change. Drawing on the expertise of the authors, many of whom have multiple years or decades of experience in the Sea Grant network, the article identifies five key strategies that Sea Grant programs employ to support the process of coastal hazards and extreme weather adaptation and resilience-building. The application of these strategies, most of which have their roots in the historical legacy of extension, are then illustrated through summaries of current Sea Grant activities and projects, showcasing how they have been applied in real-world situations. These strategies allow Sea Grant programs to fill a unique and valuable niche in national efforts to enhance coastal resilience. The article concludes with a discussion of emerging challenges and recommendations for strengthening Sea Grant’s capacity to support adaptation in coastal communities into the future.

Coastal hazard mitigation considerations: perspectives from northern Gulf of Mexico coastal professionals and decision-makers - Denise E. DeLorme; Sonia H. Stephens; Renee C. Collini (Journal of Environmental Studies and Sciences, 2022)

Utilizing an End-User Driven Process to Identify and Address Climate-Resilience Tool Needs in the U.S. Gulf of Mexico - Renee C. Collini; Mikaela C. Heming; Christina Mohrman; Melissa T. Daigle; Casey A. Fulford; Celina L. Gauthier Lowry; Marian D. Hanisko; Steven Mikulencak; Rhonda Price; Kristin R. Ransom; Tracie T. Sempier; Christine Shepard; et al. (Coastal Management, 2022)